THE CORRELATION BETWEEN STUDENTS' SELF-ESTEEM AND THEIR ENGLISH SPEAKING COMPETENCIES : A Study of Eleventh Grade Students at a Public Senior High School in Cimahi - Gustaman, Wenni Wulandari (2015)
This research paper investigated the correlation between students' self - esteem and their English speaking competencies at a Senior High School in Cimahi. The data were gathered from 62 eleventh grade students. The questionnaire of self - esteem and the speaking test were given to the students to measure the level of their self - esteem and their English speaking competencies. The scores were input in IBM SPSS 22 to find out the correlation between the two variables. The findings showed that there was a significant moderate correlation between students' self - esteem and their English speaking competencies. This study brought to a close that self - esteem also is taken into consideration to students' achievement in speaking in English. Keywords: Self - Esteem, Speaking Competencies, Self - Esteem and Language Learning. Penelitian ini meneliti tentang korelasi antara penghargaan diri dan kemampuan berbicara bahasa Inggris siswa di satu Sekolah Menengah Atas di Cimahi. Data didapatkan dari 62 siswa kelas sebelas. Kuesioner tentang penghargaan diri dan uji speaking diberikan kepada siswa untuk mengukur tingkat penghargaan diri mereka dan kemampuan berbicara bahasa Inggris nya. Data dihitung menggunakan IBM SPSS 22 untuk mengetahui korelasi antara dua variabel. Hasil menunjukkan bahwa ada korelasi yang signifikan antara penghargaan diri siswa dan kemampuan berbicara bahasa Inggris nya yang berada pada level menengah. Penelitian ini disimpulkan bahwa penghargaan diri juga termasuk kedalam keberhasilan siswa dalam berbicara menggunakan bahasa Inggris. Kata kunci: Penghargaan Diri, Kemampuan Berbicara, Penghargaan Diri dan Pembelajaran Bahasa.